2006
DOI: 10.1021/cg050679o
|View full text |Cite
|
Sign up to set email alerts
|

Constant Composition Studies Verify the Utility of the Cabrera−Vermilyea (C-V) Model in Explaining Mechanisms of Calcium Oxalate Monohydrate Crystallization

Abstract: The classic theory of Cabrera and Vermilyea (C-V) postulates that inhibition of crystallization by impurities is the result of pinning of step motion. Although generally accepted, the predictions of the C-V model have not been previously linked to studies of impurity adsorption in macroscopic crystallization systems. Since calcium oxalate monohydrate (COM) is the primary constituent of most human kidney stones, effects of impurities on COM crystallization are biologically relevant. Recent in situ atomic force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 40 publications
5
41
0
2
Order By: Relevance
“…[17] Those observations suggested that citrate inhibited COM growth by pinning step motion. Recent measurements of bulk COM growth rates [21] were consistent with that conjecture. To test this hypothesis and develop a detailed physical model of COM inhibition, we used in situ AFM to quantify the dependence of step speed on supersaturation and citrate concentration and correlate the results to a molecular-scale view of the surface.…”
supporting
confidence: 66%
“…[17] Those observations suggested that citrate inhibited COM growth by pinning step motion. Recent measurements of bulk COM growth rates [21] were consistent with that conjecture. To test this hypothesis and develop a detailed physical model of COM inhibition, we used in situ AFM to quantify the dependence of step speed on supersaturation and citrate concentration and correlate the results to a molecular-scale view of the surface.…”
supporting
confidence: 66%
“…These observations were consistent with molecular-modeling predictions of strong binding of citrate to the steps on this face [23] and led Qiu et al [23,24] to hypothesize that citrate-inhibited COM growth by binding to the step edges to create pinning sites that impeded step motion. Measurements of bulk COM growth rates by Wang et al [25] were also consistent with this picture. More recently, Weaver et al [26] showed that the dependence of COM step kinetics on citrate concentration can be understood quantitatively through the classic model of step pinning that was first proposed by Cabrera and Vermilyea (C-V) in 1958 [27], provided that model is modified to include a more realistic view of citrate adsorption dynamics, the effect of citrate on the kink site density, and an expression for the Gibbs-Thomson (G-T) effect that is correct even at high driving force, i.e., high supersaturation levels.…”
Section: Introductionsupporting
confidence: 55%
“…Small amino acids can also promote rapid transformation of amorphous CaPs into apatite [18]. However, some aspartic-acid-rich proteins and peptides could significantly inhibit the formation of calcium-based minerals [19][20][21][22][23]. Certain polyelectrolytes induced HAP crystallization at low temperatures and inhibited its nucleation at high temperatures [24].…”
Section: Nucleation and Growth Of Calcium Orthophosphate Crystals Fromentioning
confidence: 99%